A systematic review on facial detection and recognition: limitations and opportunities - Khan, Mohammad Amir; Mohd Zaki, Hasan Firdaus; Mohd Ibrahim, Azhar; Hoq, S.M Afzal; Shafie, Amir Akramin (AlamBiblio Publishers, 2024)
Face recognition technology is a biometric tool that identifies people by facial characteristics. Individuals collect the facial photography, which is then automatically processed by picture recognition software. Face detection and recognition have several potential applications in various departments like security, education, healthcare, etc. Therefore, the fundamentals and methods of broad facial detection and recognition have been discussed in this article. Owing to the outbreak of the pandemic, people are now required to wear masks so that the spreading of the coronavirus is prevented, which makes it challenging to monitor sizable crowds of mask-wearing individuals. Face masks have higher interclass similarities and interclass variability because they cover a significant portion of the face, fooling face recognition systems' facial verification process. Thus, this paper has also discussed various aspects of masked face recognition